2019
DOI: 10.3168/jds.2018-16017
|View full text |Cite
|
Sign up to set email alerts
|

Increasing dietary levels of docosahexaenoic acid-rich microalgae: Ruminal fermentation, animal performance, and milk fatty acid profile of mid-lactating dairy cows

Abstract: This study aimed to evaluate the effects of increasing dietary levels of microalgae (ALG), rich in docosahexaenoic acid (DHA; All-G-Rich, Alltech, Nicholasville, KY), in isolipidic diets, on animal performance, nutrient digestibility, ruminal fermentation, milk fatty acid profile, energy balance, microbial protein synthesis, and blood serum metabolites in mid-lactating dairy cows. Twenty-four Holstein cows [130.3 ± 15.4 d in milk, and 30.8 ± 0.543 kg/d of milk yield (mean ± standard error)] were used in a 4 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Cows were fed with different lipid sources, most of them UFA that promoted a shifts in the rumen biohydrogenation process and thereby increasing intermediate byproducts (i.e., CLA and trans-11 C18:1), and decreasing SFA (i.e., C16:0 and C18:0). Marine feedstuffs such as fish oil and microalgae have strong impacts on rumen biohydrogenation that often leads to increase in some trans C18:1 and CLA [322,325]. Dietary vegetable oils such as soybean oil often leads to changes in ruminal microbial populations and shifts in ruminal fermentation parameters affecting cellulolytic bacteria such as Fibrobacter succinogenes, Ruminococcus flavefaciens, Ruminococcus albus and Butyrivibrio fibrisolvens that are important in the biohydrogenation process of PUFA [342].…”
Section: Role Of Dietary Fatty Acids On Milk Fat Compositionmentioning
confidence: 99%
“…Cows were fed with different lipid sources, most of them UFA that promoted a shifts in the rumen biohydrogenation process and thereby increasing intermediate byproducts (i.e., CLA and trans-11 C18:1), and decreasing SFA (i.e., C16:0 and C18:0). Marine feedstuffs such as fish oil and microalgae have strong impacts on rumen biohydrogenation that often leads to increase in some trans C18:1 and CLA [322,325]. Dietary vegetable oils such as soybean oil often leads to changes in ruminal microbial populations and shifts in ruminal fermentation parameters affecting cellulolytic bacteria such as Fibrobacter succinogenes, Ruminococcus flavefaciens, Ruminococcus albus and Butyrivibrio fibrisolvens that are important in the biohydrogenation process of PUFA [342].…”
Section: Role Of Dietary Fatty Acids On Milk Fat Compositionmentioning
confidence: 99%
“…The primary objective of this study was to determine the long-term effects of feeding microalgae that is high in C22:6 n-3 on milk and plasma fat concentration of LC n-3 PUFA and animal performance over time. The cows were fed 100 g of microalgae per d as higher inclusion levels have been shown to reduce DM intake and/or result in milk fat depression (Vanbergue et al ., 2018; Marques et al ., 2019), with the consequence of a reduced milk and/or fat yield. In the current study there was no effect of dietary treatment on DM intake, which averaged 22.1 kg/d over the 14 week period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the addition of marine-derived supplements seems to be an efficient method of producing n3 PUFA-enriched milk. The results of some studies (e.g., [ 8 , 84 , 85 ]) have shown that the inclusion of microalgae in the diet of dairy cows can affected the FA profile of their milk, mainly in the content of rumenic acid and n3 FAs, the n6/n3 ratio, and the transfer efficiency of DHA from the diet into milk fat. However, in [ 86 ] it was observed that changes in milk fat composition depend on the dose of algal supplementations, e.g., graduated doses of microalgae that are rich in DHA in the diets of dairy cows resulted in reduced SFA content, whereas the proportion of PUFAs, C18:2cis9t11, and other FAs were significantly increased [ 84 ].…”
Section: Alternative and Unconventional Feeds Used In Dairy Dietsmentioning
confidence: 99%
“…The results of some studies (e.g., [ 8 , 84 , 85 ]) have shown that the inclusion of microalgae in the diet of dairy cows can affected the FA profile of their milk, mainly in the content of rumenic acid and n3 FAs, the n6/n3 ratio, and the transfer efficiency of DHA from the diet into milk fat. However, in [ 86 ] it was observed that changes in milk fat composition depend on the dose of algal supplementations, e.g., graduated doses of microalgae that are rich in DHA in the diets of dairy cows resulted in reduced SFA content, whereas the proportion of PUFAs, C18:2cis9t11, and other FAs were significantly increased [ 84 ]. In [ 8 ], the n3 FA levels were higher in microalgae-supplemented cows compared to controls, and [ 79 ] reported increased levels of DHA in the milk of cows fed a silage-based diet with microalgae supplementation.…”
Section: Alternative and Unconventional Feeds Used In Dairy Dietsmentioning
confidence: 99%